2015
DOI: 10.1159/000431180
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between Obstructive Sleep Apnea Syndrome Severity and Nesfatin-1?

Abstract: Background: Obstructive sleep apnea syndrome (OSAS) and obesity frequently occur together. The relationship between increased appetite and obesity is well known; however, despite existing knowledge about the relationship between OSAS and obesity, it is not fully understood. Objectives: This study aimed to evaluate the relationship between OSAS and the appetite-suppressing hormone nesfatin-1 independent of body mass index (BMI). Methods: A total of 134 cases were included in the study; 102 with OSAS (OSAS group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Even studies that negated progressive deterioration of untreated SDB admitted that weight change affected the natural course of SDB. 16 17 Given the known relationship between body weight and severity of SDB from cross sectional studies, 27 28 29 it seems plausible that weight gain could exacerbate SDB over time. We found no significant association between weight change and the course of SDB, and it might be due to minimal weight changes displayed by our subjects (-0.19±2.69 kg; ranged -6.0 to 8.8 kg) during the observational period.…”
Section: Discussionmentioning
confidence: 99%
“…Even studies that negated progressive deterioration of untreated SDB admitted that weight change affected the natural course of SDB. 16 17 Given the known relationship between body weight and severity of SDB from cross sectional studies, 27 28 29 it seems plausible that weight gain could exacerbate SDB over time. We found no significant association between weight change and the course of SDB, and it might be due to minimal weight changes displayed by our subjects (-0.19±2.69 kg; ranged -6.0 to 8.8 kg) during the observational period.…”
Section: Discussionmentioning
confidence: 99%
“…found that OSA patients had lower nesfatin-1 levels compared to controls. Nesfatin-1 levels negatively correlated with OSA severity 15 .…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, nesfatin-1 correlated inversely with weight, waist circumference, and BMI 13 . There is a suggestion that nesfatin-1 may even serve as an anti-obesity treatment 14,15 . The complex potential mechanisms linking OSA, obesity, hypogonadism and nesfatin-1 are depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to identify the correlation between BMI and nesfatin levels have provided contradictory results. Some of the previous studies have suggested a negative correlation between BMI and nesfatin levels [ 17 , 18 ] whereas others have suggested a positive correlation between these variables [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%